An introduction to neuroendocrinology - Wilkinson, Michael 1943- (Cambridge University Press, 2015)
How does the brain regulate sexual behavior, or control our body weight? How do we cope with stress? Addressing these questions and many more besides, this thoroughly revised new edition reflects the significant advances that have been made in the study of neuroendocrinology over the last twenty years. The text examines the importance of the hypothalamus in regulating hormone secretion from the endocrine glands, describing novel sites of hormone release including bone, heart, skeletal muscle and liver. The role of steroid hormone, neurotransmitter and peptide receptors, and the molecular responses of target tissues, is integrated into the discussion of the neuroendocrine brain, especially through changes in gene expression. Particular attention is attached to neuropeptides, including their profound influence on behavior. Complete with new full-color figures throughout, along with review and essay questions for each chapter, this is an ideal resource for undergraduate and graduate students of neuroscience, psychology, biology and physiology.